2011
DOI: 10.1007/s00535-011-0372-3
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of rebamipide plus rabeprazole for the healing of artificial ulcers after endoscopic submucosal dissection

Abstract: Treatment with a PPI plus rebamipide improved healing rates at 8 weeks for patients with ESD-derived artificial ulcer, and appeared to be particularly effective for patients with severe atrophic gastritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 21 publications
(28 reference statements)
0
66
2
Order By: Relevance
“…However, there is no current consensus regarding the optimal duration of PPI or P-CAB treatment after ESD based on the various factors that can influence healing of post-ESD ulcers. Potential predictive factors of delayed ulcer healing include the large size of artificial ulcers [9,10], the use of H2RA after ESD [5,6], preoperative fibrosis in the submucosal layer of the lesions [3], damage to the muscularis propria layer during the ESD procedure [11], location of the resected lesion in the lesser curvature [12], and lesions combined with severe atrophic gastritis [13]. However, these risk factors were identified prior to the release of P-CABs and, therefore, these studies did not consider P-CAB treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no current consensus regarding the optimal duration of PPI or P-CAB treatment after ESD based on the various factors that can influence healing of post-ESD ulcers. Potential predictive factors of delayed ulcer healing include the large size of artificial ulcers [9,10], the use of H2RA after ESD [5,6], preoperative fibrosis in the submucosal layer of the lesions [3], damage to the muscularis propria layer during the ESD procedure [11], location of the resected lesion in the lesser curvature [12], and lesions combined with severe atrophic gastritis [13]. However, these risk factors were identified prior to the release of P-CABs and, therefore, these studies did not consider P-CAB treatment.…”
Section: Introductionmentioning
confidence: 99%
“…ESD results in the creation of larger artificial ulcers. Although PPIs are the standard treatment for ESD-induced ulcers and bleeding after ESD, Fujiwara et al (9) reported that treatment with PPIs and acid-suppressive agents alone has limited effects in patients with a low level acid secretion, such as those with severe atrophic conditions in the gastric mucosa. Terano et al (4) reported that, in their study, seven weeks of rebamipide treatment without acid-suppressive agents promoted gastric ulcer healing after eradication therapy compared with a placebo.…”
Section: Discussionmentioning
confidence: 99%
“…In randomized controlled studies, rebamipide has been found to prevent nonsteroidal anti-inflammatory drug (NSAID)-induced peptic ulcers, accelerate gastric ulcer healing and suppress mucosal inflammation in patients with chronic erosive gastritis (6,7). Recently, several studies (8)(9)(10)(11)(12)(13)(14) have examined the efficacy of rebamipide and PPI combination therapy for the treatment of ESD-induced ulcers. However, there is currently no consensus regarding the optimal treatment duration or drug regimen.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several randomized controlled trials compared the combination of PPI and mucosal protective agents (being the most promising rebamipide) with PPI monotherapy in the healing of iatrogenic ulcer after ESD. The use of PPI along with rebamipide might increase ulcer healing rates because of the synergic effect of both drugs (104)(105)(106)(107). Helicobacter pylori eradication had no impact on ulcer healing at 2 months follow-up after the procedure (108,109).…”
Section: Pharmacological Treatment Only Two Randomizedmentioning
confidence: 99%